Judges' Ijtihad on Women's Rights after Divorce and its Contribution to Family Law Reform in Indonesia - Sanusi, Sanusi; Iman, Rifqi Qiwiyul; Baihaki, Reza; Farhan, Ibnu (SMART: Journal of Sharia, Traditon, and Modernity, 2023)
Women's rights in divorce cases are not regulated explicitly in the Compilation of Islamic Law. This, however, has an impact on the inequality that is adhered to in the principle of marriage law. The purpose of this article is how the ijtihad of judges regarding women's rights after divorce is contested and their contribution to family law reform in Indonesia. The method of analysis is carried out qualitatively, with a normative approach. Data analysis techniques use the theory of mubilah and mashlahat. The results of the study show that the consideration of the Panel of Judges ex officio punishing husbands for providing iddah and mut'ah maintenance, or other rights, departs from a new interpretation of the nusyuz concept which applies to both parties (men and women). Another consideration is based on Supreme Court Jurisprudence Number 137 K/AG/2007. The Panel of Judges is also based on the Supreme Court Circular Number 3 of 2017. Such a decision is a legal breakthrough. In the reading of mubilah, such a decision is in accordance with the principles of interdependence, especially in the concept of nusyuz. Such a decision is also in accordance with the principle of benefit. In the end, the renewal of Islamic family law in Indonesia is a necessity.